Emergency preparedness for infant and young child feeding in emergencies (IYCF-E): an Australian audit of emergency plans and guidance - Karleen Gribble; Mary Peterson; Decalie Brown (BMC, 2019)
Abstract Background Australia experiences a high incidence of natural emergencies and Australian governments have committed significant investment into emergency preparedness and response. Amongst the population groups most vulnerable to emergencies are infants and young children with their vulnerability centering around their specific food and fluid needs. For this reason, the World Health Assembly has urged all member states to develop and implement infant and young child feeding in emergency (IYCF-E) plans in line with international guidance. This study aimed to determine the degree to which Australia has complied with this direction by conducting an audit of Australian emergency plans and guidance. Methods Australian Federal, State/Territory and a sample of Local government emergency plans and guidance were located via web searches. Documents were searched for key words to identify content dealing with the needs of infants and young children. Plans and guidance were also searched for content dealing with the needs of animals as a comparison. Results While plans and guidance contained numerous pointers to the desirability of having plans that address IYCF-E, there was a dearth of planning at all levels of government for the needs of infants and young children. Guidance related to heat waves contained information that could prove dangerous to infants. No agency at Federal or State/Territory had designated responsibility for IYCF-E or children in general. This was in stark contrast to the situation of animals for which there was widespread and comprehensive planning at all levels of government with clear designation of organisational responsibility. Conclusions Lack of planning for IYCF-E in Australia places infants and young children at serious risk of adverse health consequences in emergencies. Australian Federal, State/Territory and Local governments need to take action to ensure that IYCF-E plans and guidance are developed and deployed in line with international standards. The pathway to successful integration of animal welfare plans provides a method for a similar integration of IYCF-E plans. Government health authorities are best placed to lead and be responsible for IYCF-E in Australia. National governments internationally should similarly take action to ensure that their youngest, most vulnerable citizens are protected in emergencies.